A review and prospects of organisational resilience research - Yue, You; Latada , Fatmawati; Pan, Bo (Journal of Islamic, Social, Economics and Development, 2025)
Based on a systematic review of existing literature, this paper first explores the definition and connotation of organisational resilience from various theoretical perspectives and summarises the factors influencing organisational resilience, including those at the individual, organisational, and network levels. Additionally, this paper offers an evaluative analysis of the dimensions used to measure organisational resilience. Building on the literature review, several directions for future research are proposed, including the collaborative mechanisms of multidimensional organisational resilience, differences in resilience-building across different types of organisations, processual studies on resilience formation, and the interactions between resilience factors at the individual, organisational, and network levels.